Management of Web-Based Human Resource Information System (HURIS) - Ruangnoi, Kritchada (2003)
Management of Web-based Human Resource Information System (HURIS) via the web site provide the most efficiently information that comes from a manageable data store. Data are likely to be managed when they are stored in a database. Organizations are now rapidly building new database applications or reengineering existing ones to take full advantage of the web as a strategic platform. This project discusses the database system development and framework for developing a prototype system for TOT Corporation Public Company Limited that has been developed by using MySQL, PHP and Apache. The system development was designed using the Unified Modeling Language (UML): high-level modeling notation for defining and designing their systems. This model acts as a reference model of the organization’s IMS. Apart from that, this project report discusses the findings and issues and challenges encountered during the development of the web database system. This prototype system was successfully being developed together with a user manual designed as a guide for the system users. It is hoped that this prototype system will contribute as a model and use as a reference in the implementation of a Web Database System for the TOT, and system prototype will be further developed and further enhanced by HR departments in TOT.